The Risk Stratification of Papillary Thyroid Cancer With Bethesda Category III (Atypia of Undetermined Significance/Follicular Lesion of Undetermined Significance) by Thyroid Fine‐Needle Aspiration Could Be Assisted by Tumor Size for Precision Treatment - Zha, Xiaojuan; Miao, Zhenchun; Huang, Xiu; Wang, Xingchun; Xie, Ruting; Jin, Jiaoying; Zou, Dajin; Yang, Peng; Huang, Yueye (Frontiers in Endocrinology, 2022)
Purpose: To investigate the clinical characteristics of papillary thyroid cancer (PTC) classified as Bethesda category III [atypia of undetermined significance (AUS)/follicular lesion of undetermined significance (FLUS)]by fine-needle aspiration (FNA) for precision treatment. Methods: A total of 1,739 patients diagnosed with Bethesda category III (AUS/FLUS) by FNA were investigated and 290 patients diagnosed with PTC were analyzed. Results: The rate of papillary thyroid microcarcinoma (PTMC) was 82.1% (238/290). The rates of lymph node metastases were 44.9% (22/49) and 25.2% (56/222) for PTC and PTMC (P=0.006). The rates of extra-thyroid extension were 46.2% (24/52) and 19.8% (47/237) (P<0.001). Compared with PTMC, PTC had significantly higher odd ratios (ORs) of 3.41 (1.81-6.44, P<0.001), 2.19 (1.16-4.13, P=0.016) and 2.51 (1.29-4.88, P=0.007) for extra-thyroid extension, multifocality and lymph node metastases after adjustment for age and gender. The larger size and BRAF V600E mutation had a robust synergistic effect for invasive features. The rates of lymph nodes metastases, multifocality and extra-thyroid extension were significantly increased with larger sizes harboring BRAF V600E mutation. Compared with PTMC harboring WT-BRAF, PTC harboring BRAF V600E mutation had adjusted higher ORs of 3.01 (1.26-8.68, P=0.015), 3.20 (1.22-8.42, P=0.018) and 5.62 (2.25-14.01, P<0.001) for lymph node metastases, multifocality and extra-thyroid extension, respectively. Conclusions: In this study, a risk stratification was recommended for patients with Bethesda category III (AUS/FLUS) nodules, with a size under 1cm harboring WT-BRAF could be regarded as low-risk and should be recommended for active surveillance. Nodules with a size over 1cm harboring WT-BRAF or those under 1cm harboring BRAF V600E mutation could be regarded as moderate risk and molecular testing should be recommended. However, those with a size over 1cm harboring BRAF V600E mutation should be regarded as high risk and a diagnostic surgery should be recommended.